Moving Beyond Short-Term Impacts of Service-Learning Study Abroad Program on Students’ Transformation: An Irish Case Study - Caroline Cully Garbers; T. Grady Roberts; Dale Pracht (Journal of International Agricultural and Extension Education, 2022)
The purpose of this study was to better understand the impacts on students who participate in short-term service-learning study abroad programs. Using Mezirow’s theory of Transformational Learning as a guide, students were interviewed on the lasting impacts that the program had on their transformation. Student participated in semi-structured interviews lasting in length of 30 minutes to an hour. These interviews took place approximately 7 months after the completion of their study abroad program. Student’s transformation was categorized into the 4 main areas of transformation according to Mezirow (1991): refining meaning schemes, learning new schemes, transforming schemes, and transforming perspectives.
Keywords: service-learning; transformational learning; faculty-led